Separator, secondary battery, and electric device

CN119343821APending Publication Date: 2025-01-21CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380046136.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-02-23
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

Existing separators cannot effectively improve the cycle performance and high-temperature storage performance of secondary batteries, resulting in a decrease in the electrochemical performance of the battery at high temperatures, and by-product migration leading to electrode damage, which limits the application of the battery.

Method used

The inorganic particles in the coating on the base film are used. The number of inorganic particles with a particle size of 2nm-50nm is not less than 50%, including ionic conductors, combined with inert fillers, to form an appropriate particle size distribution to reduce the separator impedance and improve electrochemical performance. .

Benefits of technology

By controlling the particle size distribution, inhibiting the migration of by-products, and improving the conductivity of metal ions, the cycle performance and high-temperature storage performance of the battery are significantly improved, and the service life of the battery is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119343821A_ABST
    Figure CN119343821A_ABST
Patent Text Reader

Abstract

The invention provides an isolating membrane for a secondary battery, the secondary battery and an electric device. A separator for a secondary battery includes a base film and a coating layer on at least one surface of the base film, the coating layer contains inorganic particles, the amount of inorganic particles having a particle size of 2-50 nm is not less than 50% based on the total amount of the inorganic particles in the coating layer, the inorganic particles include an ion conductor, and the ion conductor is a non-ionic conductor. The isolating membrane can improve the cycle performance and high-temperature storage performance of the secondary battery and improve the electrochemical performance of the secondary battery.
Need to check novelty before this filing date? Find Prior Art

Description

Separator, secondary battery and electrical device Technical Field

[0001] The present application relates to the technical field of secondary batteries, and in particular to an isolation membrane, a secondary battery, and an electrical device. Background Art

[0002] In recent years, secondary batteries have been widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, as well as in power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields.

[0003] Separators are a common material in secondary batteries. As a crucial component, they perform the crucial functions of separating the positive and negative electrodes, absorbing electrolyte through their porous structure, and forming an ion path. However, existing separators are unable to further enhance secondary battery performance. Therefore, there is still room for improvement.

[0004] Summary of the Invention

[0005] In view of the problems existing in the background technology, the present application provides a separator for a secondary battery, which aims to improve the cycle performance and high-temperature storage performance of the secondary battery and improve the electrochemical performance of the secondary battery.

[0006] The first aspect of the present application provides an isolation membrane for a secondary battery, comprising a base membrane and a coating located on at least one surface of the base membrane, the coating containing inorganic particles, the number content of inorganic particles with a particle size of 2nm-50nm based on the total number of inorganic particles in the coating being not less than 50%, and the inorganic particles containing ion conductors.

[0007] By controlling the number content of inorganic particles with a particle size of 2nm-50nm to be no less than 50%, the pore diameter of the diaphragm coating is made smaller than the diameter of the solvation structure of the metal ions, thereby promoting the desolvation of the solvated metal ions in the electrolyte before passing through the diaphragm, thereby inhibiting the by-products on the positive electrode side and / or the negative electrode side from migrating to the negative electrode side and / or the positive electrode side through the isolation membrane, thereby reducing the side effects on the performance of the secondary battery; at the same time, the inorganic particles contain ion conductors, which can improve the conductivity of the metal ions, reduce the impedance of the diaphragm, improve the cycle performance and high-temperature storage performance of the battery, and improve the electrochemical performance of the battery.

[0008] In any embodiment, the content of inorganic particles having a particle size of 2 nm to 50 nm is 60% to 85% by number based on the total amount of inorganic particles in the coating.

[0009] The amount and content of inorganic particles with a particle size of 2nm-50nm is within an appropriate range, which can further improve the high-temperature storage performance of the battery and improve the electrochemical performance of the battery at high temperatures.

[0010] In any embodiment, the Dn90 of the inorganic particles in the coating does not exceed 200 nm, and based on the total number of inorganic particles in the coating, the number content of inorganic particles with a particle size of 2 nm to 50 nm is 50% to 95%, and the number content of inorganic particles with a particle size greater than 50 nm is 5% to 50%.

[0011] The amount and content of inorganic particles with a particle size of 2nm-50nm and inorganic particles with a particle size greater than 50nm are within a suitable range, and the battery has excellent cycle performance and high-temperature storage performance.

[0012] In any embodiment, the Dn90 of the inorganic particles in the coating does not exceed 200 nm, and based on the total number of inorganic particles in the coating, the number content of inorganic particles with a particle size of 2 nm to 50 nm is 60% to 85%, and the number content of inorganic particles with a particle size greater than 50 nm is 15% to 40%.

[0013] The amount and content of inorganic particles with a particle size of 2nm-50nm and inorganic particles with a particle size greater than 50nm are within an appropriate range, which can improve the cycle performance and high-temperature storage performance of the battery.

[0014] In any embodiment, the Dn90 of the inorganic particles in the coating is greater than 200 nm, and based on the total number of inorganic particles in the coating, the number content of inorganic particles with a particle size of 2 nm-50 nm is 60%-80%, the number content of inorganic particles with a particle size of 50 nm-200 nm is 10%-30%, and the number content of inorganic particles with a particle size greater than 200 nm and less than or equal to 1500 nm is 10%-20%.

[0015] The number content of inorganic particles with a particle size of 2nm-50nm, the number content of inorganic particles with a particle size of 50nm-200nm, and the number content of inorganic particles with a particle size greater than 200nm and less than or equal to 1500nm are within a suitable range, and the battery has excellent cycle performance and high-temperature storage performance.

[0016] In any embodiment, the particles of the ion conductor are interconnected to form a continuous phase.

[0017] The particles of the ion conductor are interconnected to form a continuous phase, which provides a channel for the transmission of metal ions, reduces the impedance of the separator, and improves the electrochemical performance of the battery.

[0018] In any embodiment, the inorganic particles further comprise an inert filler, which is distributed in at least a portion of the gaps between the ion conductor particles to form a dispersed phase in the coating.

[0019] While the battery maintains excellent cycle performance and high-temperature storage performance, the addition of inert fillers can improve the processing performance of the coating and reduce the production cost of the coating.

[0020] In any embodiment, the inert filler has a Dv90 of 50 nm or less.

[0021] The Dv90 of the inert filler is within a suitable range, and the battery has excellent cycle performance and high-temperature storage performance.

[0022] In any embodiment, based on the total amount of inorganic particles in the coating layer, the content of the ion conductor particles is not less than 60%, and the content of the inert filler particles is not more than 40%.

[0023] When the amounts of the ion conductor and the inert filler are within a suitable range, the battery has excellent cycle performance and high-temperature storage performance.

[0024] In any embodiment, the ionic conductor comprises Li7La3Zr2O 12 、La 0.33 Li 0.557 TiO3、Li 1.5 Al 0.5 Ti 1.5 (PO4)3、Li 1.5 Al 0.5 Ge 1.5 (PO4)3、Li 10 GeP2S 12 、Na3Zr2Si2PO 12 One or more of .

[0025] In any embodiment, the ionic conductor comprises Li7La3Zr2O 12 、La 0.33 Li 0.557 TiO3、Li 1.5 Al 0.5 Ti 1.5 (PO4)3、Li 1.5 Al 0.5 Ge 1.5 (PO4)3、Li 10 GeP2S 12 、Na3Zr2Si2PO 12 One or more of the coating modification materials or doping modification materials.

[0026] In any embodiment, the inert filler comprises one or more of Al2O3, ZrO2, SiO2, Y2O2, TiO2, CaCO3, MnO2, MgO, and boehmite, and may be Al2O3 or SiO2.

[0027] In any embodiment, the base film comprises one or more of polyethylene, polypropylene, polyimide, polyethylene terephthalate, polyvinylidene fluoride, and glass fiber cloth.

[0028] A second aspect of the present application provides a secondary battery comprising the separator according to the first aspect.

[0029] In any embodiment, the secondary battery comprises a lithium ion battery or a sodium ion battery.

[0030] A third aspect of the present application provides an electrical device comprising the secondary battery of the second aspect. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] FIG1 is a schematic diagram of a diaphragm coating in one embodiment of the present application;

[0032] FIG2 is a schematic diagram of a secondary battery according to an embodiment of the present application;

[0033] FIG3 is an exploded view of the secondary battery according to one embodiment of the present application shown in FIG2 ;

[0034] FIG4 is a schematic diagram of a battery module according to an embodiment of the present application;

[0035] FIG5 is a schematic diagram of a battery pack according to an embodiment of the present application;

[0036] FIG6 is an exploded view of the battery pack shown in FIG5 according to an embodiment of the present application;

[0037] FIG. 7 is a schematic diagram of an electric device using a secondary battery as a power source according to an embodiment of the present application.

[0038] Explanation of the reference numerals: 1 battery pack; 2 upper case; 3 lower case; 4 battery module; 5 secondary battery; 51 housing; 52 electrode assembly; 53 cover plate; 6 coating; 61 first inorganic particles; 62 second inorganic particles; 63 third inorganic particles. DETAILED DESCRIPTION

[0039] Below, with appropriate reference to the accompanying drawings, the embodiments of the positive electrode active material and its manufacturing method, positive electrode slurry, secondary battery, battery module, battery pack and electrical device of the present application are specifically disclosed in detail. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0040] " scope " disclosed in the present application is limited in the form of lower limit and upper limit, and given range is limited by selecting a lower limit and an upper limit, and selected lower limit and upper limit define the boundary of special scope. The scope that this mode limits can be to include end value or not include end value, and can be arbitrarily combined, and promptly any lower limit can form a scope with any upper limit combination. For example, if the scope of 60-120 and 80-110 is listed for specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range value 1 and 2 listed, and if the maximum range value 3,4 and 5 are listed, then the following scope can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In this application, unless otherwise specified, numerical range " ab " represents the abbreviation of any real number combination between a and b, wherein a and b are all real numbers. For example, a numerical range of "0-5" indicates that all real numbers between "0-5" are listed herein, and "0-5" is simply an abbreviation for these numerical combinations. Furthermore, when a parameter is expressed as an integer ≥ 2, this is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0041] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0042] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0043] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), indicating that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0044] Unless otherwise specified, the terms "include" and "comprising" used in this application may be open-ended or closed-ended. For example, "include" and "comprising" may mean that other components not listed may also be included or that only the listed components are included.

[0045] Unless otherwise specified, the term "or" is used in this application to be inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, the condition "A or B" is satisfied if any of the following conditions are met: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0046] When secondary batteries are used or stored at high temperatures, the reaction between the positive and negative electrodes and the electrolyte continues to intensify, producing complex and diverse byproducts. The byproducts spread with the help of the electrolyte and continue to react at the other electrode, causing serious damage to the electrode and causing battery capacity decay, which limits the further application of the battery.

[0047] [Isolation film]

[0048] The present application provides an isolation membrane for a secondary battery, comprising a base membrane and a coating located on at least one surface of the base membrane, wherein the coating contains inorganic particles, and based on the total number of inorganic particles in the coating, the number content of inorganic particles with a particle size of 2nm-50nm is not less than 50%, and the inorganic particles contain ion conductors.

[0049] In some embodiments, based on the total number of inorganic particles in the coating, the number content of inorganic particles with a particle size of 2nm-50nm is not less than any one of 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, and 95%.

[0050] As used herein, the term "ionic conductor" refers to a solid substance with high ionic conductivity. In some embodiments, the ions in the ionic conductor have fast liquid-like migration characteristics and can serve as a solid electrolyte.

[0051] In some embodiments, the ionic conductor comprises Li7La3Zr2O 12 、La 0.33 Li 0.557 TiO3、Li 1.5 Al 0.5 Ti 1.5 (PO4)3、Li 1.5 Al 0.5 Ge 1.5 (PO4)3、Li 10 GeP2S 12 、Na3Zr2Si2PO 12 One or more of .

[0052] In some embodiments, the ionic conductor comprises Li7La3Zr2O 12 、La 0.33 Li 0.557 TiO3、Li1.5 Al 0.5 Ti 1.5 (PO4)3、Li 1.5 Al 0.5 Ge 1.5 (PO4)3、Li 10 GeP2S 12 、Na3Zr2Si2PO 12 One or more of the coating modification materials or doping modification materials.

[0053] Ionic conductors have excellent ionic conductivity, can effectively transfer metal ions, reduce diaphragm impedance, and have good mechanical properties, and can effectively fill gaps during dense stacking and extrusion. In addition, ionic conductors have excellent processing performance and a simple preparation process, which can reduce production costs.

[0054] In this context, the number and content of inorganic particles with a particle size of 2nm-50nm can be measured using equipment and methods known in the art, such as a Microtrac MRB S3500 series laser particle size analyzer for particle size distribution. The specific testing process is as follows: immerse the membrane in N-methylpyrrolidone (NMP) solvent for 24 hours and ultrasonicate for 2 hours to remove the membrane coating; filter the detached material powder and reimmerse it in NMP solvent for 2 hours, then ultrasonicate for 2 hours to fully disperse the particles. Repeat the ultrasonic cleaning process three or more times, vacuum filter to obtain a coated powder material, and dry it in a vacuum drying oven at 80°C for 24 hours to obtain a coated powder material. Take 0.05-2g of the coated powder material, add 10-20ml of deionized water, and ultrasonicate at 53kHz and 120W for 5 minutes to ensure complete dispersion of the sample. The sample is then measured according to GB / T19077-2016 or ISO 13320:2009 standards. The number content of inorganic particles with a particle size of 2nm-50nm is measured by the particle size distribution curve.

[0055] In some embodiments, a schematic diagram of a coating layer in an isolation membrane is shown in FIG1 . The coating layer 6 includes a plurality of inorganic particles of varying sizes, such as first inorganic particles 61 having a large particle size, second inorganic particles 62 having a medium particle size, and third inorganic particles 63 having a small particle size. By combining the various inorganic particles of varying particle sizes, the pore size of the isolation membrane can be controlled and adjusted.

[0056] By controlling the number and content of inorganic particles with a particle size of 2nm-50nm to be no less than 50%, the pore diameter of the diaphragm coating is made smaller than the diameter of the solvation structure of the metal ions, thereby promoting the desolvation of the solvated metal ions in the electrolyte, effectively inhibiting the migration of by-products generated by the positive or negative electrode on both sides of the isolation membrane, and reducing the interaction of the electrolytes on both sides of the isolation membrane. At the same time, the inorganic particles contain ion conductors, which can improve the conductivity of metal ions, reduce the impedance of the diaphragm, improve the cycle performance and high-temperature storage performance of the battery, and improve the electrochemical performance of the battery.

[0057] In some embodiments, the metal ions are lithium ions or sodium ions. In some embodiments, the ion conductor is a lithium ion conductor or a sodium ion conductor.

[0058] In some embodiments, the content of inorganic particles having a particle size of 2 nm to 50 nm is 60% to 85% based on the total amount of inorganic particles in the coating.

[0059] In some embodiments, based on the total number of inorganic particles in the coating, the number content of inorganic particles with a particle size of 2nm-50nm can be selected as any one of 60%-65%, 60%-70%, 60%-75%, 60%-80%, 60%-85%, 65%-70%, 65%-75%, 65%-80%, 65%-85%, 70%-75%, 70%-80%, 70%-85%, 75%-80%, 75%-85%, and 80%-85%.

[0060] The amount and content of inorganic particles with a particle size of 2nm-50nm is within an appropriate range, which is conducive to the desolvation of solvated metal ions in the electrolyte, inhibiting the interaction between the electrolyte of the positive electrode and the electrolyte of the negative electrode, further improving the high-temperature storage performance of the battery, and improving the electrochemical performance of the battery at high temperatures.

[0061] In some embodiments, the Dn90 of the inorganic particles in the coating does not exceed 200 nm, and based on the total number of inorganic particles in the coating, the number content of inorganic particles with a particle size of 2 nm to 50 nm is 50% to 95%, and the number content of inorganic particles with a particle size greater than 50 nm is 5% to 50%.

[0062] Herein, the term "Dn90" refers to a particle diameter corresponding to 90% of the cumulative number of particles in a particle size distribution measurement performed by a laser scattering method.

[0063] In some embodiments, the Dn90 of the inorganic particles in the coating does not exceed any one of 50 nm, 100 nm, 150 nm, and 200 nm.

[0064] In some embodiments, based on the total number of inorganic particles in the coating, the amount of inorganic particles with a particle size of 2 nm to 50 nm may be 50% to 55%, 50% to 60%, 50% to 65%, 50% to 70%, 50% to 75%, 50% to 80%, 50% to 85%, 50% to 90%, 50% to 95%, 55% to 60%, 55% to 65%, 55% to 70%, 55% to 75%, 55% to 80%, 55% to 85%, 55% to 90%, 55% to 95%, 60% to 65%, 60% to 70%, 60% to 75%. , 60%-80%, 60%-85%, 60%-90%, 60%-95%, 65%-70%, 65%-75%, 65%-80%, 65%-85%, 65%-90%, 65%-95%, 70%-75%, 70%-80%, 70%-85%, 70%-90%, 70%-95%, 75%-80%, 75%-85%, 75%-90%, 75%-95%, 80%-85%, 80%-90%, 80%-95%, 85%-90%, 85%-95%, and any one of them.

[0065] In some embodiments, based on the total amount of inorganic particles in the coating, the amount of inorganic particles having a particle size greater than 50 nm may be 5%-10%, 5%-15%, 5%-20%, 5%-25%, 5%-30%, 5%-35%, 5%-40%, 5%-45%, 5%-50%, 10%-15%, 10%-20%, 10%-25%, 10%-30%, 10%-35%, 10%-40%, 10%-45%, 10%-50%, 15%-20%, 15%-25%, 15%-30%, 15 ... 5%, 15%-40%, 15%-45%, 15%-50%, 20%-25%, 20%-30%, 20%-35%, 20%-40%, 20%-45%, 20%-50%, 25%-30%, 25%-35%, 25%-40%, 25%-45%, 25%-50%, 30%-35%, 30%-40%, 30%-45%, 30%-50%, 35%-40%, 35%-45%, 35%-50%, 40%-45%, 40%-50%, 45%-50%.

[0066] In this article, the Dn90 of inorganic particles can be tested using equipment and methods known in the art, such as a Microtrac MRB S3500 series laser particle size analyzer for particle size distribution testing. The specific testing process is as follows: the membrane is immersed in N-methylpyrrolidone (NMP) solvent for 24 hours and ultrasonicated for 2 hours to remove the membrane coating; the detached material powder is filtered and re-immersed in NMP solvent for 2 hours, followed by ultrasonication for 2 hours to fully disperse the particles. The ultrasonic cleaning process is repeated at least three times, and the coated powder material is vacuum filtered to obtain the coated powder material, which is then dried in a vacuum drying oven at 80°C for 24 hours to obtain the coated powder material. 0.05-2g of the coated powder material is taken, 10-20ml of deionized water is added, and ultrasonication is performed at a frequency of 53KHz and a power of 120W for 5 minutes to ensure that the sample is completely dispersed. The sample is then measured according to GB / T19077-2016 or ISO 13320:2009 standards. The Dn90 of inorganic particles is determined by the particle size number distribution curve.

[0067] Herein, the test method for the number content of inorganic particles with a particle size greater than 50 nm refers to the test method for the number content of inorganic particles with a particle size between 2 nm and 50 nm.

[0068] Inorganic particles with a particle size greater than 50nm have low interfacial resistance, providing a primary channel for metal ion transport. They also possess excellent mechanical properties, enhancing the strength of the separator. Inorganic particles with a particle size between 2nm and 50nm can effectively fill the pores between larger inorganic particles while bridging inorganic particles larger than 50nm, shortening the metal ion transport distance and improving the ionic conductivity of the separator. The interaction between large and small particles also enhances the wettability of the coating with the electrolyte, increasing the density of the coating from the outer layer to the inner layer. Metal ions enter the separator and undergo a gradient desolvation, enhancing the separator's mass transfer efficiency.

[0069] By combining inorganic particles with a particle size greater than 50 nm with inorganic particles with a particle size between 2 nm and 50 nm, the ionic conductivity and mechanical strength of the coating are improved, which is beneficial to the desolvation of metal ions, and enables the battery to have excellent cycle performance and high-temperature storage performance.

[0070] In some embodiments, the Dn90 of the inorganic particles in the coating does not exceed 200 nm, and based on the total number of inorganic particles in the coating, the number content of inorganic particles with a particle size of 2 nm to 50 nm is 60% to 85%, and the number content of inorganic particles with a particle size greater than 50 nm is 15% to 40%.

[0071] In some embodiments, based on the total number of inorganic particles in the coating, the number content of inorganic particles with a particle size of 2nm-50nm can be selected as any one of 60%-65%, 60%-70%, 60%-75%, 60%-80%, 60%-85%, 65%-70%, 65%-75%, 65%-80%, 65%-85%, 70%-75%, 70%-80%, 70%-85%, 75%-80%, 75%-85%, and 80%-85%.

[0072] In some embodiments, based on the total number of inorganic particles in the coating, the amount of inorganic particles having a particle size greater than 50 nm may be in the range of 15% to 20%, 15% to 25%, 15% to 30%, 15% to 35%, 15% to 40%, 20% to 25%, 20% to 30%, 20% to 35%, 20% to 40%, 25% to 30%, 25% to 35%, 25% to 40%, 30% to 35%, 30% to 40%, or 35% to 40%.

[0073] The amount and content of inorganic particles with a particle size of 2nm-50nm and inorganic particles with a particle size greater than 50nm are within an appropriate range. The cooperation between large particles and small particles can improve the cycle performance and high-temperature storage performance of the battery.

[0074] In some embodiments, the Dn90 of the inorganic particles in the coating is greater than 200 nm, and based on the total number of inorganic particles in the coating, the number content of inorganic particles with a particle size of 2 nm-50 nm is 60%-80%, the number content of inorganic particles with a particle size of 50 nm-200 nm is 10%-30%, and the number content of inorganic particles with a particle size greater than 200 nm and less than or equal to 1500 nm is 10%-20%.

[0075] In some embodiments, the Dn90 of the inorganic particles in the coating is greater than any one of 200 nm, 250 nm, 300 nm, 350 nm, 400 nm, and 450 nm.

[0076] In some embodiments, based on the total number of inorganic particles in the coating, the number content of inorganic particles with a particle size of 2nm-50nm can be selected as any one of 60%-65%, 60%-70%, 60%-75%, 60%-80%, 65%-70%, 65%-75%, 65%-80%, 70%-75%, 70%-80%, and 75%-80%.

[0077] In some embodiments, based on the total number of inorganic particles in the coating, the amount of inorganic particles with a particle size of 50nm-200nm is any one of 10%-15%, 10%-20%, 10%-25%, 10%-30%, 15%-20%, 15%-25%, 15%-30%, 20%-25%, 20%-30%, and 25%-30%.

[0078] In some embodiments, based on the total amount of inorganic particles in the coating, the content of inorganic particles having a particle size greater than 200 nm and less than or equal to 1500 nm may be any one of 10%-15%, 10%-20%, and 15%-20%.

[0079] Herein, the test method for the number content of inorganic particles with a particle size greater than 200 nm and less than or equal to 1500 nm refers to the test method for the number content of inorganic particles with a particle size of 2 nm to 50 nm.

[0080] Inorganic particles with a particle size greater than 50nm provide the primary pathway for metal ion transport. These particles possess excellent mechanical properties and can enhance the strength of the separator. Inorganic particles with a particle size between 2nm and 50nm can effectively fill the pores of the coating while bridging inorganic particles larger than 50nm, shortening the metal ion transport distance and improving the ionic conductivity of the separator. The interaction of large and small particles also enhances the wettability of the coating with the electrolyte, increasing the density of the coating from the outer layer to the inner layer. Metal ions enter the separator and undergo a gradient desolvation, enhancing the separator's mass transfer efficiency.

[0081] While the battery maintains excellent cycle performance and high-temperature storage performance, the Dn90 of the inorganic particles in the coating is greater than 200nm. The coating contains inorganic particles with a particle size greater than 200nm and less than or equal to 1500nm, which can reduce the production cost of the inorganic particles, reduce the use of binders in the coating preparation process, and reduce the production cost of the coating. In addition, the coating contains inorganic particles with relatively large particle size, which can improve the processability of the coating slurry, enhance the processability of the diaphragm, and improve production efficiency.

[0082] In some embodiments, the particles of the ion conductor are interconnected to form a continuous phase.

[0083] The particles of the ion conductor are interconnected to form a continuous phase, which provides a channel for the transmission of metal ions, reduces the impedance of the separator, and improves the electrochemical performance of the battery.

[0084] In some embodiments, the inorganic particles further comprise an inert filler, which is distributed in at least a portion of the gaps between the ion conductor particles to form a dispersed phase in the coating.

[0085] In some embodiments, the inert filler is distributed in the spaces between all the ion conductor particles, forming a dispersed phase in the coating.

[0086] While the battery maintains excellent cycle performance and high-temperature storage performance, adding inert fillers can reduce agglomeration in the coating slurry and improve the processing performance of the coating slurry. At the same time, the price of inert materials is relatively cheap, which can greatly reduce the production cost of the diaphragm.

[0087] In some embodiments, the inert filler has a Dv90 of 50 nm or less.

[0088] In some embodiments, the inert filler comprises one or more of Al2O3, ZrO2, SiO2, Y2O2, TiO2, CaCO3, MnO2, MgO, and boehmite.

[0089] The above-mentioned inert filler has the advantages of high mechanical strength, simple particle preparation and low price, which ensures that the diaphragm has excellent mechanical strength while further reducing the production cost of the diaphragm.

[0090] In some embodiments, the inert filler comprises Al2O3 or SiO2.

[0091] As used herein, the term "Dv90" refers to a particle diameter corresponding to 90% of the cumulative volume of particles in a particle size distribution measurement performed by a laser scattering method.

[0092] In this context, the Dv90 of an inert filler can be measured using equipment and methods known in the art, such as a Microtrac MRB S3500 series laser particle size analyzer. The specific testing procedure is as follows: 0.05-2g of the inert material is added to 10-20ml of deionized water. Ultrasound is then performed at 53kHz and 120W for 5 minutes to ensure complete dispersion. The sample is then measured according to GB / T19077-2016 or ISO 13320:2009. The Dv90 of the inert filler is measured using a particle size volume distribution curve.

[0093] The Dv90 of the inert filler is less than or equal to 50nm, which can ensure that the inert material is filled in the gaps between the ion conductors, prevent the ion conductors from being covered by the inert filler, and ensure the "smooth" transmission channels of metal ions, so that the battery has excellent cycle performance and high-temperature storage performance.

[0094] In some embodiments, based on the total amount of inorganic particles in the coating, the content of the ion conductor particles is not less than 60%, and the content of the inert filler particles is not more than 40%.

[0095] In some embodiments, the content of the ion conductor particles is no less than 60%, 70%, 80%, 90%, or 95% based on the total amount of inorganic particles in the coating.

[0096] In some embodiments, the inert filler comprises no more than 5%, 10%, 20%, 30%, or 40% of the total amount of inorganic particles in the coating.

[0097] By controlling the amount and content of ion conductors and inert fillers within a suitable range, the cost can be reduced while ensuring that the battery has excellent cycle performance and high-temperature storage performance.

[0098] In some embodiments, the base film comprises one or more of polyethylene, polypropylene, polyimide, polyethylene terephthalate, polyvinylidene fluoride, and fiberglass cloth, and / or one or more of a multilayer composite film of polyethylene, polypropylene, polyimide, polyethylene terephthalate, polyvinylidene fluoride, and fiberglass cloth. When the separator is a multilayer composite film, the materials of each layer can be the same or different, without particular limitation.

[0099] In addition, the secondary battery, battery module, battery pack, and electric device of the present application will be described below with reference to the drawings as appropriate.

[0100] In one embodiment of the present application, a secondary battery is provided.

[0101] Typically, a secondary battery consists of a positive electrode, a negative electrode, an electrolyte, and a separator. During the battery's charge and discharge processes, active ions are embedded in and extracted from the positive and negative electrodes. The electrolyte acts as a conductor of ions between the positive and negative electrodes.

[0102] [Positive electrode]

[0103] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector, wherein the positive electrode film layer includes a positive electrode active material.

[0104] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on either or both of the two opposite surfaces of the positive electrode current collector.

[0105] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0106] In some embodiments, the positive electrode active material may adopt a positive electrode active material for a battery that is well known in the art. As an example, the positive electrode active material may include at least one of the following materials: a lithium-containing phosphate with an olivine structure, a lithium transition metal oxide, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM333), LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM523), LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM211), LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM622), LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM811), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05 O2) and its modified compounds. Examples of olivine-structured lithium-containing phosphates may include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.

[0107] In some embodiments, the positive electrode film layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), a vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, a vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, a tetrafluoroethylene-hexafluoropropylene copolymer, and a fluorine-containing acrylate resin.

[0108] In some embodiments, the positive electrode film layer may further include a conductive agent. For example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0109] In some embodiments, the positive electrode sheet can be prepared by the following method: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components, are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode current collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.

[0110] [Negative electrode]

[0111] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer provided on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.

[0112] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on either or both of the two opposite surfaces of the negative electrode current collector.

[0113] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer base layer and a metal layer formed on at least one surface of the polymer base material. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy, etc.) on a polymer base material (such as a base material of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0114] In some embodiments, the negative electrode active material may be a negative electrode active material for a battery that is well known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxides, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxides, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.

[0115] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).

[0116] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0117] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).

[0118] In some embodiments, the negative electrode sheet can be prepared by the following method: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components, are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode current collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.

[0119] [Electrolytes]

[0120] The electrolyte conducts ions between the positive and negative electrodes. This application does not specify the type of electrolyte, and the electrolyte can be selected based on the needs. For example, the electrolyte can be liquid, gel, or solid.

[0121] In some embodiments, the electrolyte is an electrolyte solution comprising an electrolyte salt and a solvent.

[0122] In some embodiments, the electrolyte salt may be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bisfluorosulfonyl imide, lithium bistrifluoromethanesulfonyl imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium bisoxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.

[0123] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methylpropyl carbonate, ethylpropyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.

[0124] In some embodiments, the electrolyte may further include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, and additives that improve battery high or low temperature performance.

[0125] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square, or any other shape. For example, FIG2 shows a secondary battery 5 having a square structure as an example.

[0126] In some embodiments, referring to Figure 3, the outer packaging may include a shell 51 and a cover plate 53. The shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can be formed into an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, and those skilled in the art can select according to specific actual needs.

[0127] In some embodiments, secondary batteries can be assembled into a battery module. The number of secondary batteries contained in the battery module can be one or more. The specific number can be selected by those skilled in the art according to the application and capacity of the battery module.

[0128] Figure 4 shows an example battery module 4. Referring to Figure 4 , within the battery module 4, multiple secondary batteries 5 may be arranged sequentially along the length of the battery module 4. Of course, any other arrangement is also possible. Furthermore, the multiple secondary batteries 5 may be secured together using fasteners.

[0129] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.

[0130] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art based on the application and capacity of the battery pack.

[0131] Figures 5 and 6 illustrate an example battery pack 1. Referring to Figures 5 and 6 , the battery pack 1 may include a battery box and multiple battery modules 4 disposed within the battery box. The battery box comprises an upper case 2 and a lower case 3. The upper case 2 can be positioned over the lower case 3 to form an enclosed space for accommodating the battery modules 4. The multiple battery modules 4 can be arranged in any manner within the battery box.

[0132] In addition, the present application also provides an electric device, which includes at least one of the secondary battery, battery module, or battery pack provided in the present application. The secondary battery, battery module, or battery pack can be used as a power source for the electric device, and can also be used as an energy storage unit for the electric device. The electric device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but is not limited thereto.

[0133] As the electrical device, a secondary battery, a battery module or a battery pack can be selected according to its usage requirements.

[0134] Figure 7 shows an example of an electric device. This device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the high power and high energy density requirements of the secondary battery, a battery pack or battery module can be used.

[0135] Another example device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is generally required to be lightweight and thin, and may use a secondary battery as a power source.

[0136] Example

[0137] Below, the embodiment of the present application is described. The embodiment described below is exemplary and is only used to explain the present application, and is not to be construed as limiting the present application. Where specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. Reagents or instruments used that do not specify the manufacturer are conventional products that can be obtained commercially.

[0138] 1. Preparation method

[0139] Example 1

[0140] 1) Preparation of isolation membrane

[0141] The first inorganic particle Li with a Dv90 of 50nm 1.5 Al 0.5 Ti 1.5 (PO4)3(LATP) was mixed with a second inorganic particle LATP having a Dv90 of 150 nm to obtain mixed inorganic particles, wherein the mass content of the first inorganic particle was 5% and the mass content of the second inorganic particle was 95%, based on the total mass of the mixed inorganic particles. The mixed inorganic particles, polyvinylidene fluoride binder and polyethylene glycol octylphenyl ether dispersant were then mixed in a mass ratio of 95:4.5:0.5, and then N-methylpyrrolidone was added and stirred and dispersed to obtain an isolation film coating slurry. The isolation film coating slurry was coated with a double-sided coating device at a rate of 20 mg / 1540.25 cm 2 The coating weight is applied to the polyethylene base film, and after the coating is completed, it is dried, cold pressed, and slit to prepare the isolation film.

[0142] 2) Preparation of positive electrode sheet

[0143] The positive electrode active material lithium cobalt oxide, binder polyvinylidene fluoride (PVDF), and conductive agent conductive carbon black were mixed in N-methylpyrrolidone (NMP) solvent in a mass ratio of 97%: 2%: 1% to prepare the positive electrode slurry. The positive electrode slurry was coated on the surface of aluminum foil using an extrusion coater according to the positive electrode active material unit area mass requirement and dried. The coated electrode was then pressed by a cold press at a pressure of 2.5 g / cm 3 The designed compaction is cold pressed to obtain the positive electrode sheet.

[0144] 3) Preparation of negative electrode sheet

[0145] The negative electrode active material artificial graphite, the binder styrene-butadiene rubber (SBR), the conductive agent conductive carbon black, and the thickener sodium carboxymethyl cellulose (CMC) are mixed evenly in deionized water in a mass ratio of 95%:2%:1%:2% to prepare a negative electrode slurry. The slurry is coated on a copper foil, dried, and cut to obtain a negative electrode sheet.

[0146] 4) Preparation of electrolyte

[0147] In an argon atmosphere glove box (H2O<0.1ppm, O2<0.1ppm), the organic solvent ethylene carbonate (EC) / ethyl methyl carbonate (EMC) was mixed uniformly in a volume ratio of 3 / 7, 12.5% ​​LiPF6 lithium salt was added and dissolved in the organic solvent, and stirred uniformly to obtain the electrolyte of Example 1.

[0148] 5) Battery preparation

[0149] The positive electrode sheet, separator, and negative electrode sheet are stacked in order, with the separator positioned between the positive and negative electrodes to provide isolation. The cells are then wound to form a bare cell. The bare cell is then placed in an outer package, injected with the prepared electrolyte, and packaged, injected, formed, and vented to create a secondary battery.

[0150] In Examples 2 to 14 and Comparative Examples 1 to 4, the composition and content of the inorganic particles in the separator were adjusted.

[0151] 2. Performance Testing

[0152] 1. Particle size distribution test

[0153] Particle size distribution was measured using a Microtrac MRB S3500 series laser particle size analyzer. The specific testing process was as follows: the membrane to be tested was immersed in NMP solvent for 24 hours, followed by ultrasonic treatment for 2 hours to remove the membrane coating. The detached material powder was filtered and re-immersed in NMP solvent for 2 hours. The particles were then ultrasonically dispersed for 2 hours. The ultrasonic cleaning process was repeated at least three times. The coated powder was vacuum filtered and dried in a vacuum drying oven at 80°C for 24 hours to obtain the coated powder material. 0.05-2g of the coated powder material was added to 10-20ml of deionized water and ultrasonicated at 53kHz and 120W for 5 minutes to ensure complete dispersion. The sample was then measured according to GB / T19077-2016 or ISO 13320:2009 standards.

[0154] The particle size distribution curve is used to measure the number content of inorganic particles with a particle size of 2nm-50nm, the number content of inorganic particles with a particle size of 50nm-200nm, the number content of inorganic particles with a particle size greater than 200nm and less than or equal to 1500nm, and the Dn90 of the inorganic particles. Dn90 refers to the particle size corresponding to 90% of the cumulative number of particles in the particle size distribution measurement performed by laser scattering; Dv90 refers to the particle size corresponding to 90% of the cumulative volume of particles in the particle size distribution measurement performed by laser scattering.

[0155] 2. Battery performance test

[0156] 1) Cyclic performance test

[0157] The battery was allowed to stand at 25°C for 30 minutes, discharged at a constant current of 0.33C to 2.5V, allowed to stand for 5 minutes, and then charged at a constant current of 0.33C to 4.48V. Constant voltage charging was then performed to a cutoff current of 0.05C. After standing for 5 minutes, the battery was discharged at a constant current of 0.33C to 2.5V. The test cell capacity was recorded as the initial capacity (C0). After standing for 5 minutes, the above steps were repeated for the same battery. After 1500 cycles, the discharge capacity of the battery after the 1500th cycle (C1500) was recorded. The battery capacity retention rate after 1500 cycles, P1500, was calculated as C1500 / C0×100%. The test procedures for the comparative example and other embodiments were the same as above.

[0158] 2) High temperature storage capacity retention test

[0159] The battery was left to stand at 25°C for 30 minutes, discharged to 2.5V at a constant current of 0.33C, and then charged to 4.48V at a constant current of 0.33C after standing for 5 minutes. The constant voltage charge was then performed to a cut-off current of 0.05C. The battery was left to stand for 5 minutes and then discharged to 2.5V at a constant current of 0.33C. The capacity of the test cell was recorded as the initial capacity (C0). After standing for 5 minutes, the battery was charged to 4.48V at a constant current of 0.33C, and then charged to a cut-off current of 0.05C at a constant voltage. After standing for 5 minutes, the battery was transferred to a 60°C thermostat and allowed to stand for 60 minutes to raise the temperature to 60°C. The battery was taken out after being stored for 140 days, and the above method was repeated to test the reversible capacity (C140) of the battery after 140 days of storage. The storage capacity retention rate P140 of the battery after 140 days of high-temperature storage is P140=C140 / C0×100%. The test process of the comparative example and other embodiments is the same as above.

[0160] 3. Analysis of test results of various embodiments and comparative examples

[0161] Batteries of various examples and comparative examples were prepared according to the above methods, and various performance parameters were measured. The results are shown in Table 1.

[0162] Table 1 Preparation parameters and test results of examples and comparative examples

[0163] According to the above results, the secondary battery separators in Examples 1 to 14 include a polyethylene (PE) base film and a coating on at least one surface of the base film, the coating containing inorganic particles, and based on the total number of inorganic particles in the coating, the number content of inorganic particles with a particle size of 2nm-50nm is not less than 50%, and the inorganic particles contain Li 1.5 Al 0.5 Ti 1.5 (PO4)3(LATP), Li7La3Zr2O 12 (LLZO) or La 0.33 Li 0.557TiO3 (LLTO) ion conductor. Comparison of Examples 1 to 14 with Comparative Examples 1 to 4 shows that, based on the total number of inorganic particles, the number of inorganic particles with a particle size of 2 nm to 50 nm is not less than 50%, and the inorganic particles contain ion conductors, which can improve the battery's cycling performance and high-temperature storage performance, and enhance the battery's electrochemical performance.

[0164] From the comparison of Examples 2 to 3, 5 to 8 with Examples 1 and 4, it can be seen that based on the total number of inorganic particles in the coating, the number content of inorganic particles with a particle size of 2 nm to 50 nm is 60% to 85%, which can further improve the high-temperature storage performance of the battery and improve the electrochemical performance of the battery at high temperatures.

[0165] It can be seen from Examples 1 to 5 that the Dn90 of the inorganic particles in the coating does not exceed 200 nm, and based on the total number of inorganic particles in the coating, the number content of inorganic particles with a particle size of 2 nm to 50 nm is 50% to 95%, and the number content of inorganic particles with a particle size greater than 50 nm is 5% to 50%. The battery has excellent cycle performance and high-temperature storage performance.

[0166] From the comparison of Examples 2 to 3 and 5 with Examples 1 and 4, it can be seen that the Dn90 of the inorganic particles in the coating does not exceed 200 nm, and based on the total number of inorganic particles in the coating, the number content of inorganic particles with a particle size of 2 nm to 50 nm is 60% to 85%, and the number content of inorganic particles with a particle size greater than 50 nm is 15% to 40%, which can improve the cycle performance and high-temperature storage performance of the battery.

[0167] It can be seen from Examples 6 to 8 that the Dn90 of the inorganic particles in the coating is greater than 200 nm. Based on the total number of inorganic particles in the coating, the number content of inorganic particles with a particle size of 2 nm-50 nm is 60%-80%, the number content of inorganic particles with a particle size of 50 nm-200 nm is 10%-30%, and the number content of inorganic particles with a particle size greater than 200 nm and less than or equal to 1500 nm is 10%-20%. The battery has excellent cycle performance and high-temperature storage performance.

[0168] Comparing Examples 9-11 with Examples 1-8, it can be seen that the inorganic particles also contain an inert filler such as Al2O3 or SiO2. The inert filler is distributed in the gaps between the ion conductor particles, forming a dispersed phase in the coating. While maintaining excellent battery cycle performance and high-temperature storage performance, the addition of the inert filler can improve the coating's processability and reduce its production costs.

[0169] It can be seen from Examples 9 to 11 that the Dv90 of Al2O3 or SiO2 is less than or equal to 50nm, and the battery has excellent cycle performance and high-temperature storage performance.

[0170] As can be seen from Examples 9 to 11, based on the total number of inorganic particles in the coating, the particle number content of LATP is not less than 60%, the particle number content of Al2O3 or SiO2 is not more than 40%, and the battery has excellent cycle performance and high-temperature storage performance.

Claims

1. A separator for a secondary battery, characterized in that: The invention comprises a base film and a coating located on at least one surface of the base film, wherein the coating contains inorganic particles, and based on the total amount of inorganic particles in the coating, the amount of inorganic particles with a particle size of 2nm-50nm is not less than 50%, and the inorganic particles contain ion conductors.

2. The isolation film according to claim 1, characterized in that: Based on the total amount of inorganic particles in the coating, the amount of inorganic particles having a particle size of 2 nm to 50 nm is 60% to 85%.

3. The isolation membrane according to claim 1 or 2, characterized in that: The Dn90 of the inorganic particles in the coating does not exceed 200nm, and based on the total number of inorganic particles in the coating, the number content of inorganic particles with a particle size of 2nm-50nm is 50%-95%, and the number content of inorganic particles with a particle size greater than 50nm is 5%-50%.

4. The isolation membrane according to claim 1 or 2, characterized in that: The Dn90 of the inorganic particles in the coating does not exceed 200nm, and based on the total number of inorganic particles in the coating, the number content of inorganic particles with a particle size of 2nm-50nm is 60%-85%, and the number content of inorganic particles with a particle size greater than 50nm is 15%-40%.

5. The isolation film according to claim 1 or 2, characterized in that: The Dn90 of the inorganic particles in the coating is greater than 200nm. Based on the total number of inorganic particles in the coating, the number content of inorganic particles with a particle size of 2nm-50nm is 60%-80%, the number content of inorganic particles with a particle size of 50nm-200nm is 10%-30%, and the number content of inorganic particles with a particle size greater than 200nm and less than or equal to 1500nm is 10%-20%.

6. The isolation membrane according to any one of claims 1 to 5, characterized in that: The particles of the ion conductor are interconnected to form a continuous phase.

7. The isolation film according to claim 6, characterized in that: The inorganic particles further include an inert filler, which is distributed in at least a portion of the gaps between the ion conductor particles to form a dispersed phase in the coating.

8. The isolation film according to claim 7, characterized in that: The Dv90 of the inert filler is less than or equal to 50 nm.

9. The isolation membrane according to claim 7 or 8, characterized in that: Based on the total amount of inorganic particles in the coating layer, the particle number content of the ion conductor is not less than 60%, and the particle number content of the inert filler is not more than 40%.

10. The isolation membrane according to any one of claims 1 to 9, characterized in that: The ion conductor comprises Li7La3Zr2O 12 ,La 0.33 Li 0.557 TiO3、Li 1.5 Al 0.5 Ti 1.5 (PO4)3、Li 1.5 Al 0.5 Ge 1.5 (PO4)3、Li 10 GeP2S 12 、Na3Zr2Si2PO 12 One or more of .

11. The isolation membrane according to any one of claims 1 to 9, characterized in that: The ion conductor comprises Li7La3Zr2O 12 ,La 0.33 Li 0.557 TiO3、Li 1.5 Al 0.5 Ti 1.5 (PO4)3、Li 1.5 Al 0.5 Ge 1.5 (PO4)3、Li 10 GeP2S 12 、Na3Zr2Si2PO 12 One or more of the coated modified materials or doped modified materials.

12. The isolation membrane according to any one of claims 7 to 11, characterized in that: The inert filler includes one or more of Al2O3, ZrO2, SiO2, Y2O2, TiO2, CaCO3, MnO2, MgO, and boehmite, and can be Al2O3 or SiO2.

13. The isolation membrane according to any one of claims 1 to 12, characterized in that: The base film comprises one or more of polyethylene, polypropylene, polyimide, polyethylene terephthalate, polyvinylidene fluoride, and glass fiber cloth.

14. A secondary battery, characterized in that: The invention comprises the isolation film according to any one of claims 1 to 13.

15. The secondary battery according to claim 14, characterized in that: The secondary battery includes a lithium ion battery or a sodium ion battery.

16. An electrical device, characterized in that: The secondary battery according to claim 14 or 15 is included.